(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
Conflict is a process of manifestation of thought and behavior from sociocultural situations in every society. It is seen as a complex situation between two or more people. However, in alternative justice, the perspective of the conflict has an understanding, management and solution based on dialogue and communication between the people involved, which encourages protagonism, empowerment and legitimacy of the people to resolve their own conflict. This document aims to address the generalities of the conflict in order to consolidate a culture of peace, coexistence and well-being among the subjects immersed in a society in which the management and solution of the conflict is applied in a constructive and collaborative way for the construction of capable citizens to make the transition to a better society.